Reactions of fluoroalkenes with an aluminium(I) complex - Bakewell,C; White,AJP; Crimmin,MR (Angewandte Chemie International Edition, 2018)
A series of industrially relevant fluoroalkenes react with a monomeric AlI complex. These reactions break strong sp2 and sp3 C-F bonds, and result in the formation of a diverse array of organoaluminium compounds. Mechanistic studies show that two mechanisms are likely in operation: 1)direct oxidative addition of the C-F bond to AlI occurs with retention of alkene stereochemistry, and 2)stepwise formation and decomposition of a metallocyclopropane intermediate occurs with inversion of alkene stereochemistry. As part of this mechanistic analysis, we have isolated the first aluminium metallocyclopropane complex from oxidative addition of an alkene to AlI . Remarkably this reaction is reversible and reductive elimination of the alkene occurs at higher temperature reforming AlI . Furthermore, in selected cases the organoaluminium products are susceptible toward β-fluoride elimination to yield a double C-F activation pathway.